Practical approaches to rural ecological value realization: a cash study of the China palletized ecological project - Zhu, Qirong; Chen, Shaojun; Li, Xue (Frontiers in Environmental Science, 2025)
This study investigates the ecological resource development of terraced fields in Dongluo Village, China, by analyzing the historical dynamic analysis of the village’s ecological value evolution. It aims to identify practical strategies for rural ecological development and explores the multiple logics underlying the realization of rural ecological value. This study constructs a three-dimensional (3D) analytical framework of government, market, and society. The studies highlighted the role of government in providing institutional support through policy formulation and resource integration. The markets contribute by optimizing the allocation of ecological dividends and driving economic transformation. Meanwhile, society enhances the social legitimacy of ecological projects via multi-stakeholder cooperation and interest articulation. These interactions enable the activation and transformation of rural ecological value, and further provide useful experience for the construction of ecological civilization.